2010
DOI: 10.1177/155005941004100405
|View full text |Cite
|
Sign up to set email alerts
|

ERP Generator Patterns in Schizophrenia during Tonal and Phonetic Oddball Tasks: Effects of Response Hand and Silent Count

Abstract: Greater left than right reductions of P3 amplitude in schizophrenia during auditory oddball tasks have been interpreted as evidence of left-lateralized dysfunction. However, the contributions of methodological factors (response mode, stimulus properties, recording reference), which affect event-related potential (ERP) topographies, remain unclear. We recorded 31-channel ERPs from 23 schizophrenic patients and 23 age- and gender-matched healthy controls (all right-handed) during tonal and phonetic oddball tasks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 99 publications
2
14
0
Order By: Relevance
“…However, some other studies that relied on similar protocols did report lower P300 amplitudes on patients with schizophrenia (e.g. Kayser et al, 2010;Kim et al, 2003). Further, Ford et al (2000) studied the effect of the type of task (button press vs. count) on the reduction and symmetry of P300 in schizophrenia, reporting no effects or interactions relating to the type of task.…”
Section: Discussionmentioning
confidence: 93%
“…However, some other studies that relied on similar protocols did report lower P300 amplitudes on patients with schizophrenia (e.g. Kayser et al, 2010;Kim et al, 2003). Further, Ford et al (2000) studied the effect of the type of task (button press vs. count) on the reduction and symmetry of P300 in schizophrenia, reporting no effects or interactions relating to the type of task.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, methodological improvements for the CSD techniques have been very rare and slow. One obvious exception to this limitation is the work by Kayser, Tenke and Colleagues, who have innovated some methods, for example, to extract PCA components of the CSD (Kayser and Tenke, 2003; Tenke and Kayser, 2005) and successfully implemented this approach to study clinical domains (Kayser et al, 2006, 2009, 2010a,b,c, 2012, 2013, 2014; Tenke et al, 2008, 2010, 2011). Other concerns of CSD are related to its methodological limitations, which may be addressed by future studies: 1) the transformation of the EEG potentials into the CSD leads to a partial data loss, since the low-spatial-frequency (LSF) components are attenuated (Hjorth, 1980; cf.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In order to unravel the subprocesses of verbal working memory deficits in schizophrenia, Kayser et al (2006) used the CSD method in a visual word serial position task and found that schizophrenic patients showed reduced left inferior parieto-temporal P3 sources. Using tonal and phonetic oddball tasks, Kayser et al (2010a) studied ERP generator patterns as elicited by temporal PCA to examine the earlier findings showing left-lateralized dysfunction in schizophrenics with greater left than right reductions of P3 amplitude, and found a bilateral reduction in fronto-central N2 sinks and parietal P3 sources. In another study, using visual continuous recognition memory tasks with common words or unknown faces, Kayser et al (2010b) investigated whether the visual recognition memory deficits in schizophrenics were restricted to only words.…”
Section: Schizophreniamentioning
confidence: 99%
“…The distinct FRN topography, consisting of its defining mid-frontal sink (negativity) accompanied by off-midline centroparietal sources (positivity), has been observed as a stimulus- as well as a response-locked CSD component across a variety of visual and auditory ERP paradigms, including tonal and phonetic oddball tasks (e.g., Kayser and Tenke, 2006a, 2006b, Kayser et al, 2010a), dichotic oddball (Tenke et al, 2008), novelty oddball (Tenke et al, 2010), and recognition memory (Kayser et al, 2007, 2010b), and interpreted as an index of ongoing motivational or action-monitoring processes. Importantly, the centroparietal source is impacted by the response requirements, being asymmetric for left or right hand responses (i.e., larger over the ipsilateral hemisphere; cf.…”
Section: Discussionmentioning
confidence: 99%